1997
DOI: 10.1021/bi9612982
|View full text |Cite
|
Sign up to set email alerts
|

The Iron−Sulfur Clusters 2 and Ubisemiquinone Radicals of NADH:Ubiquinone Oxidoreductase Are Involved in Energy Coupling in Submitochondrial Particles

Abstract: The iron-sulfur clusters 2 and ubisemiquinone radicals of NADH: ubiquinone oxidoreductase are involved in energy coupling in submitochondrial particles van Belzen, R.; Kotlyar, A.B.; Moon, N.; Dunham, W.R.; Albracht, S.P.J. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…The electrochemical potential around -150 mV across the inner mitochondrial membrane therefore drives the three fundamental functions of mitochondria, namely ATP generation, Ca 2+ uptake/storage, and generation/detoxification of ROS (27,(35)(36)(37).…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…The electrochemical potential around -150 mV across the inner mitochondrial membrane therefore drives the three fundamental functions of mitochondria, namely ATP generation, Ca 2+ uptake/storage, and generation/detoxification of ROS (27,(35)(36)(37).…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…The number of reported ubiquinone binding sites varies depending on the author but the consensus right now is 3 binding sites (69). Two semiquinones are readily detectable by EPR (135)(136)(137) and there may be as many as three operational Q cycles (68,69,135,136,138). Several mechanisms have been proposed to explain the 4H § electron stoichiometry.…”
Section: Production At Complex Imentioning
confidence: 99%
“…The structural information, that is, the general shape of the complex and position of the iron sulfur clusters, is not arbitrary but based on experimental evidence. The distance relationships between the semiquinones and the iron sulfur proteins, as well as the general placement of the subunits, are based on EPR (68,(135)(136)(137). Both models predict the existence of Qo-type sites, defined earlier as quinol oxidation sites facing the intermembrane space (139).…”
Section: Production At Complex Imentioning
confidence: 99%
“…A series of studies of the inhibition mechanism of MPP ϩ analogues by Singer and colleagues (6 -10) have suggested that MPP ϩ analogues are bound at two sites in the enzyme, one accessible to relatively hydrophilic inhibitors (termed the "hydrophilic site") and one shielded by a hydrophobic barrier on the enzyme (the "hydrophobic site"), and that occupation of both sites is required for complete inhibition. This concept may be helpful in elucidating the terminal electron transfer step in complex I and seems to be consistent with the existence of two EPR-detectable species of complex I-associated ubisemiquinones (11,12). Some experimental results with ordinary complex I inhibitors (13-16) can be explained by assuming the existence of more than one inhibitor (or ubiquinone) binding site.…”
mentioning
confidence: 62%